Investigating the influence of high temperatures on the cycling stability of a LiNi0.6Co0.2Mn0.2O2 cathode using an innovative electrolyte additive. (10th May 2017) - Deng, Bangwei; Wang, Hao; Ge, Wujie; Li, Xiang; Yan, Xinxiu; Chen, Tao; Qu, Meizhen; Peng, Gongchang
Highlights: The Li/NCM cyclability with 1 wt.% diphenyldimethoxysilane is improved at 55 °C. Electrolyte decomposition and transition metals dissolution on NCM are reduced. DPDMS might scavenge HF and PF5 content via its Si-O bond. Abstract: Temperature is an important factor influencing the electrochemical performance of lithium ion (Li-ion) cells, higher temperature always result to worser performance of Li-ion cells. To deal with this problem, diphenyldimethoxysilane (DPDMS) was introduced into a 1 M LiPF6 -based EC:EMC:DMC (1:1:1, by volume) electrolyte due to its multifunctional Si-O bonds. Adding 1 wt.% DPDMS greatly increased the capacity retention of a Li/LiNi0.6 Co0.2 Mn0.2 O2 (Li/NCM622) half-cell at 55 °C (93.3% after 200 cycles). Cyclic voltammetry and electrochemical impedance spectroscopy measurements cconfirmed that the polarization and impedance of the cells were largely reduced upon adding DPDMS. X-ray photoelectron spectroscopy, attenuated total reflectance Fourier transform infrared spectroscopy, and inductively coupled plasma emission spectroscopy measurements demonstrated that DPDMS alleviates the electrolyte decomposition and the dissolution of transition metals on the cathode surface; the results also indicated that the Si-O bond of DPDMS plays an important role in modifying the cathode electrolyte interface by complexing with HF or PF5 species in the electrolyte. Additionally, the presence of 1 wt.% DPDMS greatly minimized the potential drop of Li/NCM622 half-cell in high-temperature storage tests and the electrolyte maintained a stable pH value after storage for 21 days. These results provide further evidence for the improved electrochemical performance of cells containing DPDMS.